2019
DOI: 10.1515/znb-2019-0047
|View full text |Cite
|
Sign up to set email alerts
|

Structural elucidation of two new compounds from Artemisia ordosica and their antioxidative activity

Abstract: Two new compounds, namely, arteordosin A (1) and arteordosin B (2), were isolated from the CHCl3 extract of Artemisia ordosica. This is the first report on the structure elucidation of arteordosin A (1) and arteordosin B (2) based on spectroscopic methods including electrospray ionization mass spectrometry, one-dimensional (1D) nuclear magnetic resonance spectroscopy (NMR) and 2D NMR techniques. Antioxidant activities of the compounds were measured for their radical scavenging capacity using 2,2-diphenyl-1-pic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…A. ordosica contains many bioactive compounds, which encompass polyphenols, flavonoids, terpenoids, essential oil and polyacetylenes (Zhang et al, 2017;Wang et al, 2019;Zhou et al, 2019). Numerous studies have demonstrated that A. ordosica has anti-inflammatory, antimicrobial (Xiao et al, 2020;Tang et al, 2021), antioxidant (Wu et al, 2019) and immunoregulatory (Xing et al, 2019) properties. Previous reports have indicated the potential benefits of A. ordosica aqueous extract (AOE) as a natural phytogenic feed additive with antioxidant potential.…”
Section: Introductionmentioning
confidence: 99%
“…A. ordosica contains many bioactive compounds, which encompass polyphenols, flavonoids, terpenoids, essential oil and polyacetylenes (Zhang et al, 2017;Wang et al, 2019;Zhou et al, 2019). Numerous studies have demonstrated that A. ordosica has anti-inflammatory, antimicrobial (Xiao et al, 2020;Tang et al, 2021), antioxidant (Wu et al, 2019) and immunoregulatory (Xing et al, 2019) properties. Previous reports have indicated the potential benefits of A. ordosica aqueous extract (AOE) as a natural phytogenic feed additive with antioxidant potential.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical constituents of A. ordosica are abundant and diverse, including flavonoids [ 16 ], terpenes [ 17 , 18 ], polysaccharides, sterols [ 19 ], coumarins [ 20 ], phenylpropanoids [ 17 ], organic acids, amino acids, and microelements [ 15 ]. In recent years, some compounds have been isolated, including a new lignan glycoside (artemordolignan glycoside A) [ 21 ], a new coumarin having a new skeleton (arteordocoumarin A) [ 22 ], four new compounds (arteordoyn A, arteordoyn B, arteordosin A, and arteordosin B) [ 23 , 24 ], and five polyacetylenes (capillene, capillinol, capillin, trans-dehydromatricaria ester, and cis-dehydromatricariaria ester) [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…After isolation, some compounds and crude essential oils exhibit reasonable repellent and fumigant activity [ 25 ]. For instance, arteordosin A and B showed antioxidant activities and could be potentially used as an antihyperlipidemic agent in routine clinical practice [ 23 ]. The inhibition rates of A. ordosica acetone extract against Fusarium oxysporum, Colletotrichum lagenarium , Botrytis cinerea , and Alternaria solani were more than 70%.…”
Section: Introductionmentioning
confidence: 99%